PENGARUH WIRAUSAHA TERHADAP PENGEMBANGAN KARIR INDIVIDU PADA DISTRIBUTOR MULTI LEVEL MARKETING DI KOTA KEDIRI - Heru Sutapa (Universitas Islam Kadiri, 2020)
The quality of an entrepreneur can be found by evaluating his/ her personality, particularly his/ her own related experience and background to find his/ her skills and competence and to create initiatives to become an entrepreneur. The objective of this analytic observasional study was to identify the influence of entrepreneurship on individual’s career development among multilevel marketing. The study involved MLM distributor in Kota Kediri. Data were analyzed with SPSS programme for Windows Results showed that most of those distributors were career development oriented. Career development was found to beinfluenced by entrepreneurship